Perbedaan Kadar Insulin-Like Growth Factor-1 dan Tumor Necrosis Factor-α Serum pada Berbagai Derajat Sarkopenia Pasien Lanjut Usia: Studi Potong Lintang - Tamayo, Auliangi; Mulyana, Roza; Martini, Rose Dinda (UI Scholars Hub, 2023)
Introduction. Sarcopenia is a phenomenon of progressive decline in muscle function that occurs due to the aging process. Insulin-like growth factor-1 (IGF-1) and tumor necrosis factor-α (TNF-α) have an important role in the occurrence of sarcopenia as a positive and negative regulator of muscle mass. Research shows differences in IGF-1 and TNF-α levels between sarcopenia and non-sarcopenia groups, but research on differences in severity of sarcopenia remains unclear. The purpose of this study was to determine the difference in levels of IGF-1 and TNF-α in various degrees of sarcopenia in elderly patients. Methods. This was an analytical observational study with a cross-sectional approach involving 45 subjects of elderly patients who came to the internal outpatient clinic of RSUP dr. M. Djamil Padang and met the criteria for inclusion and exclusion. Subjects were grouped into possible sarcopenia, sarcopenia, and severe sarcopenia. Then, serum IGF-1 and TNF-α examinations were performed using the enzyme linked immunosorbent assay (ELISA) method. Data was analyzed using SPSS 26.0. Results. Median of serum IGF-1 levels in the total sample were 41.36 ng/mL. The highest levels of IGF-1 were found in the possible sarcopenia group (55.28 ng/mL), while the lowest level was in the severe sarcopenia group (31 ng/mL). Median of serum TNF-α levels in the total sample were 157.63 ng/L with the lowest was found in the possible sarcopenia group (111.41 ng/L) and the highest was in the severe sarcopenia group (241.1 ng/L). There was a significant difference in serum levels of IGF-1 and TNF-α in the three sarcopenia groups (p= 0.001). IGF-1 levels decreased according to the severity of sarcopenia, while TNF-α levels increased according to the severity of sarcopenia. Conclusions. There are differences in serum levels of IGF-1 and TNF-α between possible sarcopenia, sarcopenia, and severe elderly sarcopenia.